A trust value sharing scheme in heterogeneous identity federation topologies - Liu, Ning (2021)
Recent developments in heterogeneous identity federation systems have heightened the need for the related trust management system. The trust management system evaluates, manages, and shares users’ trust values. The service provider (SP) members of the federation system rely on users’ trust values to determine which type and quality of service will be provided to the users. While identity federation systems have the potential to help federated users save time and energy and improve service experience, the benefits also come with significant privacy risks. So far, there has been little discussion about the privacy protection of users in heterogeneous identity federation systems. In this paper, we propose a trust value sharing scheme based on a proxy ring signature for the trust management system in heterogeneous identity federation topologies. The ring signature schemes can ensure the validity of the data and hide the original signer, thereby protecting privacy. Moreover, no group manager participating in the ring signature, which naturally matches with our decentralized heterogeneous identity federation topologies. The proxy signature can reduce the workload of the private key owner. The proposed scheme shortens the calculation time for verifying the signature and then reduces the overall time consumption in the process of trust sharing. Our studies prove that the proposed scheme is privacy-preserving, efficient, and effective.